2003
DOI: 10.1038/sj.bjc.6600945
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer in a large cohort of nonaspirin NSAID users: a population-based study

Abstract: There is increasing evidence of an inverse association between use of nonsteroidal anti-inflammatory drugs (NSAIDs) and risk of colorectal cancer. However, data regarding other cancer sites are limited. Using data from the population-based North Jutland Prescription Database and the Danish Cancer Registry, we compared cancer incidence among 172 057 individuals prescribed nonaspirin NSAIDs with expected incidence (based on county-specific cancer rates) during a 9-year study period. A total of 6081 incident canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
209
6
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(227 citation statements)
references
References 40 publications
(62 reference statements)
10
209
6
2
Order By: Relevance
“…Several epidemiologic studies have suggested that long-term users of NSAIDs (Non-Steroidal Anti-Inflammatory Drugs) have a lower risk of colorectal cancers compared to nonusers. [28][29][30] Although observations are less compelling NSAIDs may also have a protective effect against certain non-gastrointestinal cancer such as cancers of the lung, 31 prostate, 32 breast 31,33,34 and ovary. 29,35 The suggested inverse association between NSAIDs usage and cancer risk is compatible with the reduced risk of cancers of the digestive, respiratory and genital organs observed in the present investigation but not with the increased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiologic studies have suggested that long-term users of NSAIDs (Non-Steroidal Anti-Inflammatory Drugs) have a lower risk of colorectal cancers compared to nonusers. [28][29][30] Although observations are less compelling NSAIDs may also have a protective effect against certain non-gastrointestinal cancer such as cancers of the lung, 31 prostate, 32 breast 31,33,34 and ovary. 29,35 The suggested inverse association between NSAIDs usage and cancer risk is compatible with the reduced risk of cancers of the digestive, respiratory and genital organs observed in the present investigation but not with the increased risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded retrospective analyses (Rosenberg 1995;Harris et al, 2002;Moysich et al, 2002;Muscat et al, 2003) because of potential biases in aspirin recall and selection of controls and the observed heterogeneity of results from case-control and cohort studies in previous reviews. We also excluded prospective studies that did not account for smoking (Paganini-Hill et al, 1989;Friis et al, 2003;Sorensen et al, 2003) or had no quantitative measure of aspirin use (Shreinemachers and Everson, 1994;Ratnasinghe et al, 2004) because these factors likely influence the association between aspirin and lung cancer. After exclusions, we identified nine studies that met our criteria for inclusion in the review (see Table 4).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) used in relation to lung cancer have been investigated in at least 20 studies, including four hospital-based case -control studies (Rosenberg, 1995;Harris et al, 2002;Moysich et al, 2002;Muscat et al, 2003), fourteen cohort studies (Paganini-Hill et al, 1989;Thun et al, 1993;Schreinemachers and Everson, 1994;Langman et al, 2000;Akhmedkhanov et al, 2002;Friis et al, 2003;Holick et al, 2003;Sørensen et al, 2003;Ratnasinghe et al, 2004;Skriver et al, 2005;Hayes et al, 2006;Hernández-Diaz and Rodriguez, 2007;Jacobs et al, 2007;Wall et al, 2007) and three randomised trials (Peto et al, 1988;Lee et al, 1995;Cook et al, 2007). Significantly decreased risks were observed in three of the four hospital-based case -control studies (Rosenberg, 1995;Harris et al, 2002;Moysich et al, 2002), although all were based on selfreported drug use after diagnosis of cancer, raising the possibility of recall bias.…”
mentioning
confidence: 99%